2016
DOI: 10.1097/acm.0000000000001054
|View full text |Cite
|
Sign up to set email alerts
|

All Health Is Global Health, All Medicine Is Social Medicine: Integrating the Social Sciences Into the Preclinical Curriculum

Abstract: As physicians work to achieve optimal health outcomes for their patients, they often struggle to address the issues that arise outside the clinic. Social, economic, and political factors influence patients' burden of disease, access to treatment, and health outcomes. This challenge has motivated recent calls for increased attention to the social determinants of health. At the same time, advocates have called for increased attention to global health. Each year, more U.S. medical students participate in global h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…Residents should be exposed to social paediatrics so that they can learn to address the social determinants of health and appreciate the importance of the individual clinician to advocate on behalf of patients and their communities [19]. This mapping methodology was helpful in identifying key aspects relevant to social pediatric learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residents should be exposed to social paediatrics so that they can learn to address the social determinants of health and appreciate the importance of the individual clinician to advocate on behalf of patients and their communities [19]. This mapping methodology was helpful in identifying key aspects relevant to social pediatric learning.…”
Section: Resultsmentioning
confidence: 99%
“…For our study we chose to evaluate both the intended and formal curriculum of social pediatric education. Since social pediatrics is often viewed as less important than biomedical science and technology in medical education, we also explored the “hidden curriculum” of social paediatrics [19]. The overall aim of this study was to determine and characterize social pediatric education in our pediatric residency training in order to understand strengths and gaps.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, Kasper and colleagues outline three critiques that medical students at Harvard Medical School present when discussing the boundaries of their clinical mandate. The 'antisocial' critique argues that clinicians should not be called upon to do the work of 'social workers, economists and politicians' (Kasper et al 2016). The 'pragmatic' critique argues that any knowledge outside of that which will ensure success as a clinician (technical knowledge) is irrelevant; and the 'local' critique argues that there is no need to learn about health issues elsewhere if one will work solely in the United States.…”
Section: Competing Valuesmentioning
confidence: 99%
“…In a survey of American scholars in the fields of preventive medicine, community medicine and public health, conducted during the period from August 1965 to March 1966, it was found that the majority of respondents preferred social medicine as the name of their field of study [20]. Papers on social medicine continued to be published, although not many, discussions on social medicine education began, and practical changes took place as well [21-23]. Recently, on April 30, 2016, the Social Medicine Consortium composed of individuals, universities and organizations striving for equity in health held a symposium on social medicine at the University of Minnesota, exemplifying the current perception of and interest in social medicine in the US [24].…”
Section: The Origins Concepts and International Diffusion Of Social mentioning
confidence: 99%